(untitled) (Tidsskrift for Praktisk Teologi, 2019)
Chaplaincy in Norway has changed considerably from the 1950s. The number of chaplaincy positions has increased, although if it is seen on the background of expansion in healthcare and other public services, the increase is moderate. Several important developments have happened: A move from a “religious service” model to a “existential care” model has gradually taken place; the work of chaplains has increasingly been underpinned by a professionalisation; and a considerable volume of scientific research has been performed by chaplains – contributing to an evidence base for the activities. Alongside, the increasingly multireligious and secular profile of the population has affected the practice field in which the chaplains offer services. Recent innovations in chaplaincy give reasons to optimism in this field.